First-trimester diagnosis and management of Cesarean scar pregnancies after in vitro fertilization-embryo transfer: a retrospective clinical analysis of 12 cases. Issue 1 (December 2015) - Ouyang, Yan; Li, Xihong; Yi, Yan; Gong, Fei; Lin, Ge; Lu, Guangxiu
Abstract Background Although Caesarean scar pregnancy (CSP) is rare, it can cause life-threatening complications. The increasing rate of Cesarean delivery plus rapid development of in vitro fertilization-embryo transfer (IVF-ET) may increase the occurrence of CSP as well as the ratio of heterotopic CSP (HCSP)/CSP. Therefore, early diagnosis and management of CSP are necessary to avoid serious complications. And the purpose of this article is to evaluate the importance and feasibility of the first-trimester diagnosis and management of CSP after IVF-ET. Methods All the 12 cases were secondary infertility patients who had a history of Cesarean section and underwent IVF-ET in our reproductive center. All cases with CSP were diagnosed using transvaginal color Doppler sonography (TVS). Medical, surgical and expectant managements were implemented, and the management results were traced. Results Patients with CSP (n  = 12) were diagnosed from January 2011 to April 2015, 6 (50 %) of which were HCSP. The prevalence of CSP was 1:1688 pregnancies. The gestational age ranged from 5 + 3 to 7 + 4 weeks in all CSP, and from 5 + 6 to 7 + 4 weeks in HCSP at diagnosis. Five patients received successful surgical treatment. The success rate of medical and expectant management was 50 % (1/2) and 100 % (5/5), respectively. One patient with failed medical management needed an emergency laparotomy to evacuate CSP. The uterus was preserved in all 12 patients. Conclusions The Caesarean section and IVF-ET may increase the ratio of HCSP/CSP. TVS is a noninvasive and effective tool for use in diagnosing CSP. CSP should be carefully excluded in patients who have had a history of Caesarean section. Early diagnosis of CSP in the first trimester may contribute towards the preservation of uterus as well as intrauterine pregnancy (IUP) in HCSP.